Good Governance and Institutional Reforms : Catalysts for Trade Growth in Singapore - Burkova, Mariia (2025)
This thesis "Good Governance and Institutional Reforms: Catalysts for Trade Growth in Singapore" explores how institutional reforms have shaped Singapore’s trade performance and economic growth over time. Using both qualitative analysis and regression models, it examines which institutions played a central role, and how principles like transparency and accountability contributed to long-term trade stability. The study finds that institutional quality, especially in digital customs systems and legal enforcement, strongly correlates with increased trade volume and foreign direct investment. The Singaporean model, while not directly transferable, offers insights that may be adapted by other small, open economies.